Impact of Flood on Education in Darakeswar Mundeswari-Interfluve in Hugli District, West Bengal - Mandal, Soumen; Jana, N. C. (National Geographical Journal of India, 2022)
Education is an important indicator of human development in any region. However, Educational institutions have been greatly affected due to recurrent flood problems in Darakeswar-Mundeswari Interfluve. In the present paper, an attempt has been made to assess the impact of flood on education keeping in view the physical and socio-economic background of the study area. In addition, some measures have also been suggested for the development of education in such a flood-prone area.